Overexpression of SoCYP85A1 Increases the Accumulation of Castasterone and Confers Enhanced Black Shank Tolerance in Tobacco Through Modulation of the Antioxidant Enzymes’ Activities - Duan, Fangmeng; Song, Wenwen (Frontiers in Plant Science, 2019)
Black shank caused by Phytophthora parasitica var. nicotianae is one of the most devastating diseases in tobacco production. In this study, we characterized a novel cytochromic resistance gene, SoCYP85A1, from spinach, which was upregulated in response to P. parasitica var. nicotianae infection. Overexpression of SoCYP85A1 in tobacco resulted in remarkable resistance to pathogen inoculation, with diverse resistance levels in different transgenic lines. Meanwhile, a significant accumulation of castasterone (CS) was detected in transgenic plants when challenged with the pathogen. Moreover, activities of antioxidant enzymes were enhanced by SoCYP85A1 in the transgenic lines as compared to those in the wild types inoculated with P. parasitica var. nicotianae. In addition, the alteration of CS content resulted in interference of phytohormone homeostasis. Overall, these results demonstrate that SoCYP85A1 can participate in the defense response to P. parasitica var. nicotianae through the involvement of defense enzymes and by interaction with certain phytohormones. Our findings suggest that SoCYP85A1 could be used as a potential candidate gene for improving resistance to black shank disease in tobacco and other economic crops.